Silica-based Nano-coating on Zirconia Surfaces Using Reactive Magnetron Sputtering: Effect on Chemical Adhesion of Resin Cements - Cavalcanti Queiroz, Jose Renato [UNESP]; Massi, Marcos; Nogueira, Lafayette [UNESP]; Silva Sobrinho, Argemiro Soares da; Bottino, Marco Antonio [UNESP]; Oezcan, Mutlu (Quintessence Publishing Co Inc, 2013)
Purpose: To compare the effect of silica (Si)-based nano-coating deposited by reactive magnetron sputtering (RMP) with that of conventional surface conditioning using metal/zirconia primer alone or after air-particle abrasion on the adhesion of resin cements to zirconia ceramic.Materials and Methods: Two hundred forty zirconia ceramic blocks (Cercon) were sintered, finished with 1200-grit SiC paper under water cooling, and cleaned ultrasonically in distilled water for 10 min. The blocks (4.5 mm x 3.5 mm x 4.5 mm) were randomly divided into 24 groups (n = 10) according to 3 testing parameters: a) resin cements (Multilink, Panavia F, RelyX U100), b) surface conditioning (no conditioning as control group; Metal/Zirconia Primer; air abrasion + Metal/Zirconia Primer; Si-based nanofilm + Monobond s); c) aging (no aging vs thermo cycling at 5 degrees C to 55 degrees C, 6000 cycles). The nanofilm was deposited by direct current using argon/oxygen plasma (8:1 in flux) on the zirconia surface. Resin cements were bonded to zirconia surfaces using polyethylene molds. The shear bond strength (SBS) test was performed using a universal testing machine (1 mm/min), and after debonding, the substrate and adherent surfaces were analyzed using optical and scanning electron microscopes to categorize the failure types. The data were statistically evaluated using 3-way ANOVA and Tukey's test (5%).Results: Resin cement type (p < 0.05), surface conditioning method (p < 0.05), and aging condition (p < 0.05) had a significant effect on the bond strength results. Interactions were also significant (p < 0.05). In the nonaged condition, while control groups presented the lowest results with all cements (0 to 5.2 MPa), the air-abraded group in combination with RelyX U100 resulted in the highest SBS (21.8 +/- 6.7 MPa). After aging, the SBS results decreased in the air-abraded groups for all cements (4.54 to 9.44 MPa) and showed no statistical significance compared to the Si-based nanocoated groups (4.24 to 6.44 MPa). After air-abrasion and primer application, only Panavia F and RelyX U100 cements showed exclusively mixed failures, but after nanofilm coating and silanization, all cements showed exclusively mixed failures with and without aging.Conclusion: Chemical adhesion of the resin cements tested to zirconia was similar after silica-based nanofilm deposition and air abrasion followed by primer application.
Keywords: adhesion; bond strength; nanocoating; nanofilm; plasma coating; reactive magnetron sputtering; silica; Y-TZP; zirconia; zirconia primer